2018
DOI: 10.1101/476747
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long read-based de novo assembly of low complex metagenome samples results in finished genomes and reveals insights into strain diversity and an active phage system

Abstract: BackgroundComplete and contiguous genome assemblies greatly improve the quality of subsequent systems-wide functional profiling studies and the ability to gain novel biological insights. While a de novo genome assembly of an isolated bacterial strain is in most cases straightforward, more informative data about co-existing bacteria as well as synergistic and antagonistic effects can be obtained from a direct analysis of microbial communities. However, the complexity of metagenomic samples represents a major ch… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 98 publications
0
15
0
Order By: Relevance
“…In contrast, single-molecule sequencing platforms such as the Oxford Nanopore MinION, GridION and PromethION are able to sequence very long fragments of DNA (>10 Kbp, with over 2 Mbp reported) [4,5] and with recent improvements to the platform making metagenomic studies using nanopore more viable, such studies are increasing in frequency [6,7,8,9]. Long reads help with alignment-based assignment of taxonomy and function due to their increased information content [10,11].…”
mentioning
confidence: 99%
“…In contrast, single-molecule sequencing platforms such as the Oxford Nanopore MinION, GridION and PromethION are able to sequence very long fragments of DNA (>10 Kbp, with over 2 Mbp reported) [4,5] and with recent improvements to the platform making metagenomic studies using nanopore more viable, such studies are increasing in frequency [6,7,8,9]. Long reads help with alignment-based assignment of taxonomy and function due to their increased information content [10,11].…”
mentioning
confidence: 99%
“…Wick and Holt, 2019 recently benchmarked various long-read assemblers and demonstrated that Flye improves on other long-read assemblers in the case of bacterial genomes. Since this conclusion was further confirmed in recent bacterial studies (Ring et al, 2018, Schmid et al, 2018, Somerville et al, 2019, we only analyzed how mosaicFlye improves on the Flye and metaFlye (Kolmogorov et al, 2019b) assemblies in the case of bacterial genomes and metagenomes. In the case of the human genome, we analyzed both Canu and Flye assemblies.…”
Section: Resultsmentioning
confidence: 66%
“…Some of the limitations to obtain complete genomes using high-throughput sequencing (HTS) are mainly due to the shorter reads produced. Short reads not only can impair the detection of different viral haplotypes (Takeda et al, 2019) and introduce ambiguities in de novo assemblies (Schatz et al, 2010) but are also unable to resolve complex regions of the genome (Somerville et al, 2019;Treangen and Salzberg, 2011). Additionally, the PCR amplification steps involved during library preparation can introduce considerable bias, for example selective amplification and chimeras (Ardui et al, 2018;Ng et al, 2018).…”
Section: Introductionmentioning
confidence: 99%